2021
DOI: 10.1007/s11442-021-1906-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional modelling of soil organic carbon density and carbon sequestration potential estimation in a dryland farming region of China

Abstract: Soil organic carbon density (SOCD) and soil organic carbon sequestration potential (SOCP) play an important role in carbon cycle and mitigation of greenhouse gas emissions. However, the majority of studies focused on a two-dimensional scale, especially lacking of field measured data. We employed the interpolation method with gradient plane nodal function (GPNF) and Shepard (SPD) across a range of parameters to simulate SOCD with a 40 cm soil layer depth in a dryland farming region (DFR) of China. The SOCP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Thus, the calculation of SOC stocks based exclusively on surface horizons implies leaving as much as three quarters of the total SOC out of the SOC models, and somewhat less than 60% if the calculation is based on information from the top 30 cm. In this regard, Sun et al [53] indicate currently existing inaccuracies, as the SOC stock models are essentially based on two dimensions; that is, they take only one value of the surface layer as representative of the soil as a whole without considering the vertical effect, and they lack the SOC estimation based on data measured at different depths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the calculation of SOC stocks based exclusively on surface horizons implies leaving as much as three quarters of the total SOC out of the SOC models, and somewhat less than 60% if the calculation is based on information from the top 30 cm. In this regard, Sun et al [53] indicate currently existing inaccuracies, as the SOC stock models are essentially based on two dimensions; that is, they take only one value of the surface layer as representative of the soil as a whole without considering the vertical effect, and they lack the SOC estimation based on data measured at different depths.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the main hypothesis of this work, according to which, sampling focused on the topsoil excludes most of the total SOC stock. This may lead to significant underestimations of current stocks of SOC, which may affect models of the future evolution of SOC [50][51][52] or soil carbon sequestration potential [53], since the mineralization of the C stocks will be slower than other dryland soils in similar conditions. These constraints determine insufficient knowledge of C stocks in critical regions, such as agricultural drylands, regarding the effects of climate change on these regions [54].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we quantified the threshold value of SOC ranging from 0.07 g/kg to 11 g/kg in potential suitable areas as well. Soil organic carbon (SOC) reflects the ability of sequestration of carbon, directly affecting the maintenance and improvement of soil fertility and, thus, is often recognized as an important index to evaluate soil fertility [65]. Cheng et al [66] demonstrated differences in grape composition associated with soil water and organic carbon.…”
Section: Discussionmentioning
confidence: 99%